Key factors and use cases of servant leadership driving organizational performance - Pressentin, Maria, 1969- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book provide findings and recommendations to support practical application of servant leadership theory for the 21st Century economy, leveraging a multi-regional context, with the goal of developing cohesive high performing teams, purposeful and engaging environments, build trust and organization vitality"--